2011
DOI: 10.1007/s11099-011-0016-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of photosynthetic characteristics of hulless barley at two altitudes on the Tibetan Plateau

Abstract: To determine the photosynthetic characteristics of C 3 plants and their sensitivity to CO 2 at different altitudes on the Tibetan Plateau, hulless barley (Hordeum vulgare L. ssp. vulgare) was grown at altitudes of 4,333 m and 3,688 m. Using gas-exchange measurements, photosynthetic parameters were simulated, including the maximum net photosynthesis (P max ) and the apparent quantum efficiency (α). Plants growing at higher altitude had higher net photosynthetic rates (P N ), photosynthesis parameters (P max and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The measurements took place at the middle of the ear leaf during normal weather conditions with sunshine and no rain in summer, between 9:00–12:00 in the morning. Based on the literatures [ 28 30 ] and the actual circumstances, the conditions supported were as follows: photosynthetic photon flux density of 1800 μmol m -2 s -1 , CO 2 concentration of 400 μmol mol -1 , air temperature of 30°C and relative air humidity of 0% (0% moisture from air to the leaf chamber).…”
Section: Methodsmentioning
confidence: 99%
“…The measurements took place at the middle of the ear leaf during normal weather conditions with sunshine and no rain in summer, between 9:00–12:00 in the morning. Based on the literatures [ 28 30 ] and the actual circumstances, the conditions supported were as follows: photosynthetic photon flux density of 1800 μmol m -2 s -1 , CO 2 concentration of 400 μmol mol -1 , air temperature of 30°C and relative air humidity of 0% (0% moisture from air to the leaf chamber).…”
Section: Methodsmentioning
confidence: 99%
“…The photosynthetic ability of plants growing in cool climates is more sensitive to temperature (Fan et al . ). Thus, a plant's metabolism is severely reduced at low temperatures (Davies & Albrigo ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is suggested that the temperature is an important factor that affects plant physiology (Allen & Ort 2001). The photosynthetic ability of plants growing in cool climates is more sensitive to temperature (Fan et al 2011). Thus, a plant's metabolism is severely reduced at low temperatures (Davies & Albrigo 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The photosynthetic behaviour of alpine plants is often influenced by environmental conditions. There have been various studies on altitudinal trends for photosynthesis with increased (Fan et al, 2011; Wieser et al, 2010) or decreased (Qi et al, 2020) in different plants.…”
Section: Introductionmentioning
confidence: 99%